The evolution of larval developmental mode: insights from hybrids between species with obligately and facultatively planktotrophic larvae. Issue 5 (14th July 2015) - Armstrong, Anne Frances; Lessios, Harilaos A.
SUMMARY: Life history characteristics play a pervasive role in the ecology and evolution of species. Transitions between feeding and non‐feeding larval development have occurred many times in both terrestrial and marine phyla, however we lack a comprehensive understanding of how such shifts occur. The sea biscuits Clypeaster rosaceus and Clypeaster subdepressus employ different life history strategies (facultatively feeding larvae and obligately feeding larvae, respectively) but can hybridize. In this study, we examined the development of hybrid larvae between these two species in order to investigate the inheritance of larval developmental mode. Our results show that both reciprocal hybrid crosses developed via the feeding mode of their maternal species. However, as feeding larvae can obtain both energy and hormones from algal food, we tested how hormones alone affected development by setting up a treatment where we added exogenous thyroid hormone, but no food. In this treatment the offspring of all four crosses (two homospecific and two heterospecific crosses) were able to metamorphose without algal food. Therefore we hypothesize that although hybrid developmental mode was inherited from the maternal species, this result was not solely due to energetic constraints of egg size.